ANTESEDEN KINERJA KARYAWAN BANK SYARIAH DI MALANG RAYA - Achmad Sani Supriyanto; Vivin Maharani Ekowati (Politeknik Negeri Batam, 2019)
Organizational Citizenship Behavior (OCB) is a behavior that has an effect on organizational effectiveness. It has important consequences in workplace. OCB can contribute to organizational effectiveness through improved performance, enabling organizations to adapt to environmental change, and strengthening coordination within working groups. Therefore, it is important to investigate the variables that can improve the OCB. This study aims to determine the direct effect of spiritual leadership on employee’s performance, identifying the role of OCB to mediate the effect of spiritual leadership on employee’s performance. The population is all 436 employees of Sharia banking with state-owned status in Malang Raya, consist of Bank Sharia Mandiri, BRI Sharia, BTN Sharia and BNI Sharia. Total 140 samples selected are all permanent employees calculated by using Slovin formula. Data is collected directly from respondents by questionnaires and analyzed by PLS. The research results show that spiritual leadership has n0 effect on performance. OCB mediates the effect of Entrepreneur leadership on performance.